Gender Diversity and Sustainability Performance: The Role of Financial Technology Adoption as Moderator - Dwiyanjana Santyo Nugroho; Anita (Ilomata International Journal of Tax and Accounting, 2023)
This research is intended to explore the influence of gender diversity on financial and bank environmental performance. In addition, in order to strengthen the impact of gender diversity on financial performance and environmental performance, this research also tests the moderating effect of financial technology adoption. The population in this study examines banks that received the 2022 Digital Banking Awards, which is the research period from 2017-2022. The proportion of women on the Board of Commissioners and the Board of Directors is a proxy for gender diversity. This research method uses random effect models and fixed effect models in regression equations that test financial performance. Meanwhile, the regression model that tests environmental performance uses logit regression. This study shows that the percentage of females on boards has an impact on financial results, but not on environmental performance. The financial and environmental performance is not affected by the gender ratio in the board of directors. Other results show that, although financial technology can enhance the influence of women's representation on boards regarding environmental performance, but it does not have an impact on financial performance. On the other hand, the impact on financial and environmental performance of the proportion of women on the board of directors is not reduced by the adoption of financial technology. The implications of these findings provide input for regulators to determine the threshold for women's involvement on the board of directors.